1992
DOI: 10.1111/j.1600-0528.1992.tb01694.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk indicators and potential risk factors for caries in 5‐year‐olds of different ethnic groups in Amsterdam

Abstract: The aim of this study was threefold: first, to assess the oral health of Turkish, Moroccan, Surinamese, Dutch and "other" 5-yr-old children living in Amsterdam; second, to identify risk indicators for caries, in addition to ethnicity; and third, to identify potential risk factors related to differences in caries experience in these children. Results showed the mean dmfs scores of Turkish and Moroccan children to be much higher than that of the Dutch and Surinamese children; 8.1 and 8.2 versus 3.6 and 3.4, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 5 publications
7
30
0
Order By: Relevance
“…Male children had higher scores of dmfs compared to female children in the study; this observed gender difference was also found in some other studies examining prevalence of dental caries in preschool children in First Nation communities in Canada [27], a cross sectional study in Brazil [28] and another study studying different ethnic groups in Amsterdam [29]. None of the studies suggested any reason for the gender differences, however it has been postulated that female adolescents consider oral appearance more important than males and perhaps this may be a motivating factor in younger children as well [30].…”
Section: Discussionsupporting
confidence: 85%
“…Male children had higher scores of dmfs compared to female children in the study; this observed gender difference was also found in some other studies examining prevalence of dental caries in preschool children in First Nation communities in Canada [27], a cross sectional study in Brazil [28] and another study studying different ethnic groups in Amsterdam [29]. None of the studies suggested any reason for the gender differences, however it has been postulated that female adolescents consider oral appearance more important than males and perhaps this may be a motivating factor in younger children as well [30].…”
Section: Discussionsupporting
confidence: 85%
“…Secondly, we do not know for how long the parents had practised the stated regimen. The age of the child when the parents started to brush its teeth is no doubt equally or even more important [Verrips et al, 1992] and, unfortunately, that was not asked for. Notably, little is known about the actual toothbrushing habits in preschool children.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings raise provocative research questions about the underlying basis for increased risks that could be associated with cultural norms including concern for oral health, prenatal diet that could contribute to enamel hypoplasia, care of primary teeth, child rearing practices, and access to dental and medical care. The studies also suggest that ethnic minorities may experience significant barriers to dental care, including cost of care and availability of accessible services (45,52,54).…”
Section: Race and Ethnicitymentioning
confidence: 98%